KERAGAMAN KOMUNITAS TUMBUHAN DI TAMAN NASIONAL GUNUNG CIREMAI - Junaedi, Decky Indrawan (Buletin Kebun Raya, 2008)
Research on vegetation characteristics and vegetation community similarities was conducted in Mount Ciremai National Park. Three vegetation communities found in the southern part of this National Park, i.e. Parigi-Paguyangan Badak-Acip area (PPA), Karamat Purnajiwa area (KP) and Karamat Sanghiang area (KS), Kuningan, West Java, were investigated. Quadrant method with 10 observation plots per ha was used for vegetation analysis whereas the Jaccard and Sorensen similarity indices were used to evaluate community similarities among the three locations. Vegetation community in PPA (1.100 â 1.580 m asl) was highly dominated by Castanopsis argentea (saninten). This was quite different with the vegetation communities of KP and KS (1.000 â 1.200 m asl) that were dominated by Horsfieldia glabra (kalapa ciung) and several other co-dominant species, such as Sterculia sp., Ficus benjamina and Ficus glabella. Further analysis using Jaccard Similarity Index (lsj) showed that the vegetation communities of KP and KS had a relatively high similarity.